NAVIGATING DISTANCE METASTASES IN MULTIFOCAL BREAST CANCER - Munira Kh. Norbekova,; Lola T. Alimkhodzhaeva ,; Sherzod I. Ruziyev ,; Mohinabonu J. Khusanova , (Central Asian Journal of Medicine, 2025)
Purpose of the study: to analyze the process of tumor metastasis in patients with multifocal breast cancer (BC). Material and method: a retrospective analysis of data from 133 patients treated at the Republican Specialized Scientific and Practical Center of Oncology and Radiology and its branches during the period 2018-2023. Results: Conclusion: for patients with multifocal characteristics, the frequency of tumor involvement in regional lymph nodes is higher; however, there is practically no difference compared to unifocal tumors in terms of metastasis to distant organs.